The relationship between monthly air pollution and violent crime across the United States. Issue 2 (2nd April 2020) - Burkhardt, Jesse; Bayham, Jude; Wilson, Ander; Berman, Jesse D.; O'Dell, Katelyn; Ford, Bonne; Fischer, Emily V.; Pierce, Jeffrey R.
ABSTRACT: Recent evidence suggests a relationship between short-term pollution exposure and crime, with a particular emphasis on aggressive behavior. However, the previous analyses are limited in geographic scope. In this paper, we estimate the effect of fine particulate air pollution (PM 2.5 ) exposure on crime across 99% of counties in the contiguous United States. We combine monthly data on crime, PM 2.5, and satellite-derived smoke plumes for a ten-year period. We use adjusted satellite-based landscape fire smoke plume data as an instrument for overall changes in P M 2.5 . Our findings are consistent with previous research and suggest that increases in P M 2.5 raise violent crime rates, and specifically assaults. Our results indicate the effect is relatively homogeneous across the U.S. However, we find the effect is positively correlated with county median age, suggesting older populations are more susceptible to changes in air pollution. Our results indicate a need for more research on the physiological and social mechanisms behind the measured effects.